Biodegradation of the artificial sweetener acesulfame in biological wastewater treatment and sandfilters. (1st March 2017) - Castronovo, Sandro; Wick, Arne; Scheurer, Marco; Nödler, Karsten; Schulz, Manoj; Ternes, Thomas A.
Abstract: A considerable removal of the artificial sweetener acesulfame (ACE) was observed during activated sludge processes at 13 wastewater treatment plants (WWTPs) as well as in a full-scale sand filter of a water works. A long-term sampling campaign over a period of almost two years revealed that ACE removal in WWTPs can be highly variable over time. Nitrifying/denitrifying sequencing batch reactors (SBR) as well as aerobic batch experiments with activated sludge and filter sand from a water works confirmed that both activated sludge as well as filter sand can efficiently remove ACE and that the removal can be attributed to biologically mediated degradation processes. The lab results strongly indicated that varying ACE removal in WWTPs is not associated with nitrification processes. Neither an enhancement of the nitrification rate nor the availability of ammonium or the inhibition of ammonium monooxygenase by N -allylthiourea (ATU) affected the degradation. Moreover, ACE was found to be also degradable by activated sludge under denitrifying conditions, while being persistent in the absence of both dissolved oxygen and nitrate. Using ion chromatography coupled with high resolution mass spectrometry, sulfamic acid (SA) was identified as the predominant transformation product (TP). Quantitative analysis of ACE and SA revealed a closed mass balance during the entire test period and confirmed that ACE was quantitatively transformed to SA. Measurements of dissolved organic carbon (DOC) revealed an almost complete removal of the carbon originating from ACE, thereby further confirming that SA is the only relevant final TP in the assumed degradation pathway of ACE. A first analysis of SA in three municipal WWTP revealed similar concentrations in influents and effluents with maximum concentrations of up to 2.3 mg/L. The high concentrations of SA in wastewater are in accordance with the extensive use of SA in acid cleaners, while the degradation of ACE in WWTPs adds only a very small portion of the total load of SA discharged into surface waters. No removal of SA was observed by the biological treatment applied at these WWTPs. Moreover, SA was also stable in the aerobic batch experiments conducted with the filter sand from a water works. Hence, SA might be a more appropriate wastewater tracer than ACE due to its chemical and microbiological persistence, the negligible sorbing affinity (high negative charge density) and its elevated concentrations in WWTP effluents. Graphical abstract: Highlights: Acesulfame was biodegraded during wastewater and water treatment. Biodegradation of acesulfame occurred under oxic and denitrifying conditions. No relationship between the degradation rate and nitrifying activity was found. Sulfamic acid was identified as the main biotransformation product of acesulfame. Sulfamic acid is proposed as a new conservative wastewater tracer.